2019
DOI: 10.1152/physiolgenomics.00032.2019
|View full text |Cite
|
Sign up to set email alerts
|

Profiling the rainbow trout hepatic miRNAome under diet-induced hyperglycemia

Abstract: Carnivorous rainbow trout exhibit prolonged postprandial hyperglycemia when fed a diet exceeding 20% carbohydrate content. This poor capacity to utilize carbohydrates has led to rainbow trout being classified as “glucose-intolerant” (GI). The metabolic phenotype has spurred research to identify the underlying cellular and molecular mechanisms of glucose intolerance, largely because carbohydrate-rich diets provide economic and ecological advantages over traditionally used fish meal, considered unsustainable for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 80 publications
0
12
0
Order By: Relevance
“…However, teleost fish are generally considered to be glucose intolerant (4) . An excess proportion of carbohydrates in their diet causes metabolic disturbance, including decreased growth performance (5) , persistent hyperglycaemia (6) and excess lipid deposition (7,8) . The glucose regulation mechanism in fish has been discussed in numerous studies; however, until now, most metabolic genes related to carbohydrate/glucose utilisation have been found to be conserved in vertebrates (9) .…”
mentioning
confidence: 99%
“…However, teleost fish are generally considered to be glucose intolerant (4) . An excess proportion of carbohydrates in their diet causes metabolic disturbance, including decreased growth performance (5) , persistent hyperglycaemia (6) and excess lipid deposition (7,8) . The glucose regulation mechanism in fish has been discussed in numerous studies; however, until now, most metabolic genes related to carbohydrate/glucose utilisation have been found to be conserved in vertebrates (9) .…”
mentioning
confidence: 99%
“…One of the metabolic disorders caused by HCD is the persistent hyperglycemia in fish [6,21]. To address whether the addition of B. amy SS1 to the HCD had a metabolic protective effect, the fasting glucose levels were detected.…”
Section: The Addition Of B Amy Ss1 To the Hcd Decreased Glucose Levementioning
confidence: 99%
“…An excess proportion of carbohydrates in their diet causes metabolic syndrome, including decreased growth performance [5], persistent hyperglycemia [6], and excess lipid deposition [7,8]. The glucose regulation mechanism in fish has been discussed in numerous studies; however, until now, most metabolic genes related to carbohydrate/glucose utilization have been found to be conserved in vertebrates [9].…”
Section: Introductionmentioning
confidence: 99%
“…Transcriptome sequencing (RNA-Seq) is one of the most effective method to provide insight on gene expression and relevant molecular pathways of species under specific condition with high resolution and sensitivity (Kostyniuk et al, 2019;Li et al, 2017). In recent years, using RNA-Seq to study the transcriptome response of aquatic animals under ammonia stress found that ammonia can significantly affect the gene expression profile (Gupta et al, 2014;Wolf, 2013).…”
mentioning
confidence: 99%
“…It is reported to be sensitive to environmental changes (including ammonia, temperature, dissoluble oxygen and so on), which lead to their differential expression (Bizuayehu et al, 2015;Kostyniuk et al, 2019). Numerous studies have shown that differential expression of miRNA is one of the most key factors in regulating expression of target gene in aquatic animals to adapt to the environment (Sun et al, 2020).…”
mentioning
confidence: 99%